HUBUNGAN PENGETAHUAN DAN SIKAP TERHADAP PERILAKU REMAJA TENTANG KEHAMILAN PRANIKAH DI PERUMAHAN PERMATA TANGERANG RW 20 - Fuadi, Allif; Zubairi, Ahmad; Septimar, Zahrah Maulidia (Nusantara Hasana Journal, 2022)
Knowledge is a process of remembering and recognizing objects that have been studied well through the five senses in a particular field. Attitude is a pattern of behavior, anticipatory tendencies or readiness, predisposition to adapt in social situations. Behavior is a way of acting that shows a person's behavior or the activities of humans themselves which have a very wide range, including: walking, crying, laughing, writing, reading, and so on. One of the factors that can influence premarital sexual behavior is knowledge. In addition to knowledge of the lack of good attitudes and understanding of sexual behavior can be detrimental to teenagers themselves as well as their families.. Methods: Descriptive correlation research design aims to find out the relationship of knowledge and attitudes towards adolescent behavior about premarital pregnancy in Perumahan Permata Tangerang RW 20. Selection of subjects using the Total Sampling method. The sample numbered 134 people. Data analysis using Chi-Square. Results: The results of the analysis of adolescent knowledge and behavior relationships based on the chi-square test obtained a p-value of 0.850 > 0.05 which means there is no relationship between knowledge and adolescent behavior. While the relationship of adolescent attitudes and behavior obtained a p-value of 0.067 > 0.05 which means there is no relationship between adolescent attitudes and behavior Conclusion: The high knowledge and attitude of a person usually has sexual behavior that is not at risk, while the low knowledge and attitude of a person will have risky sexual behavior.